(untitled) (Research, Society and Development, 2020)
Granulated activated carbon (CAG) is widely used in filters of chemical respiratory devices to retain organic solvents, acid gases, ammonia and hydrogen sulfide. Its use is due to its high area / mass ratio, which gives it a large surface of adsorption of gaseous contaminants, which can vary between 300 and 1,300 m2g-1 depending on the raw material used in its manufacture, chemical treatment. and dimensions. The objective of this work was to develop a methodology using an experimental arrangement consisting of a circuit to cause saturation of a semifacial respiratory filter (SF) using a organic solvente and this way measure the adsorptive capacity (Ca) of the CAG. Under assay conditions, with toluene as solvent, the Ca value obtained was 110.2 mg.g-1. The model presented provided a useful parameter for manufacturers and useers as an indicator for quality control of chemical filters used in semifacial respiratory devices, allowing the comparison between batches of GACs originated from different raw materials, shapes and dimensions.